EFFECT EVALUATION OF PAIN RELIEF USING EXTERNAL RADIATION TECHNIQUE IN BONE METASTATIC CANCER PATIENTS AT MILITARY HOSPITAL 175 - Nguyen Thanh , Cong; Ngo Dang , Huong; Phan The , Nhat; Do Thi , Hung (Tạp chí Y Dược Thực hành 175, 2024)
Objective: Evaluate the effectiveness of pain relief due to bone metastasis using external beam radiation therapy technique. Subjects and Methods: Retrospective and prospective study describing 178 patients with stage IV cancer, bone metastases, treated for pain relief with external radiotherapy, at the Institute of Oncology and Nuclear Medicine, Hospital Military Medicine 175, from May 2021 to April 2022. Results: Patients’ mean age was 58.47 years old. The majority of patients were men (62.9%), primary lung cancer (54.5%), osteolytic lesions (80.3%), primary cancer with multifocal bone metastases (89, 9%). The proportion of patients responding to pain treatment after external radiotherapy at 1 week, 2 weeks, 4 weeks and 8 weeks was 40.4%, 76.4%, 88.8% and 85.9%, respectively. The pain relief response rate in the radiotherapy group combined with second- and third-line analgesics was highest at week 4 (56.2% and 32.6%). The average pain score of patients decreased significantly in both single-focal bone metastasis and multi-focal bone metastasis groups at 4 weeks and 8 weeks after radiotherapy treatment.